A Ramesside Administrative Document (P. Cambridge University Library MS. Add. 4167) - Hagen, Fredrik (Zeitschrift für ägyptische Sprache und Altertumskunde, 2008)
The article presents a previously unpublished Ramesside administrative papyrus from the Cambridge University Library (P. CUL MS. Add. 4167). The document is a list of food and drink given to various named individuals, mainly controllers and their wives, as well as a stable master, 'by the hand of′ several soldiers. Its social context is not known, but it may be connected with riverbank trading. Photographs, transcription and translation with commentary are included.